Water depth modulates the species richness–biomass relationship in submerged macrophytes - Wen, Zihao; Wang, Hao; Shan, Hang; Cao, Yu; Tan, Lu; Zhu, Tianshun; Cai, Qinghua; Ni, Leyi; Zhang, Xiaolin; Chou, Qingchuan; Cao, Te (Frontiers in Environmental Science, 2023)
The effect of biodiversity on ecosystem productivity has been a controversial issue in ecological research. The species richness-productivity relationship is highly variable in natural ecosystems, with a positive relationship being one of the most commonly observed relationships. Previous regional studies from terrestrial ecosystems have demonstrated that environmental gradients can regulate the species richness-productivity relationship. However, how this relationship varied in freshwater ecosystems across spatial environment gradients remains unclear. In this study, we propose that the species richness-productivity relationship can be modulated by water depth. Here, we surveyed the submerged macrophyte community structure by establishing 24 transects and 642 quadrats in the Erhai Lake, Yunnan Plateau, China. Our findings highlight that the species richness-productivity relationship gradually changed from slightly positive to strong positive as the environment became more light-limited with increasing water depth, supporting the stress-gradient hypothesis. Results from this study provide new insights into the biodiversity-ecosystem functioning relationships and in managing lake macrophyte communities and productivity.